Fertilizer development and price in international perspective - Stone, Bruce (International Food Policy Research Institute, 1987)
Fertilizer use in Bangladesh exceeded 540,000 metric tons of nutrients in 1983/84 and 1985/B6. In 1984/85 it reached 596,311 tons. In terms of materials, this was more than 1.26 million metric tons. Thus from 1983/84 to 1985/86 applications of manufactured nutrients ranged from 63 to 70 kilograms per hectare of net cultivated area and from 41 to 46 kilograms per hectare of total cropped area. l The view that Bangladesh's fertilizer consumption is among the world's lowest is inaccurate. While fertilizer consumption per hectare in Bangladesh is considerably lower than in many developed countries, it is higher than average levels in a large number of developing countries.